ANALISIS TITIK PULANG POKOK USAHA PETERNAKAN AYAM RAS PETELUR CV. MENARA DI KOTA PALU - Al Alamsyar; Abdul Muis; Sulaeman Sulaeman (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
This study aimed to determine therevenue and break-even point obtained by laying chicken farm of CV. Menara and as well asthe margin of safety that should be achieved in order to keep    the business profitable. Primary and secondary data was collected on June till Agustus 2014.       The primary datawas determined by observation and interview tofour respondentsusing quistionniare tools.  The secondary data was references obtained from related institution. The data was analyzed using qualitative, break-even point and margin of safety analysis.The results show that the break-even point of CV  Menara was reached at 13,539egg sales at the price of IDR 31,000 rack-1.mThe eggs were produced by 40,000 chickens with the total production cost was               IDR. 730,919,167 and the revenue wasIDR 806.000.000.  In June 2014,the revenue of the farm   was above the break-even point.  The value of margin of safety was 48%. Meanwhile, in July 2014, the break-even point of the farm was reached at 9,430 egg sales at the price ofIDR 34,000 rack-1 produced by 40,000 chickens with the total production cost of IDR 730,519,167 and revenues of IDR 870,400,000. The value of margin of safety on the farm in July was 63 %.Key Words : Analysis Break-even Point, Broiler Laying, Margin of Safety.